파랑관통형 고속 활주선 실선 성능 분석에 관한 연구 - 정우철(Uh-Cheul Jeong); 이창우(Chang-Woo Lee); 한상천(Sang-Chun Han) (Han-guk haeyang gonghak hoeji (Online), 2017)
This study investigated the sea trial performance of a wave piercing high speed planing hull (WPH). The bow shape of the boat is sharp, and it has no chine or spray strip like a normal planing boat. The skeg is attached to the bottom of the boat in the longitudinal direction from the bow to the stern. The speed performance was analyzed as the speed dropped in a wave, and the seakeeping performance was compared with that of a planing boat with a similar velocity coefficient by measuring the vertical acceleration of the bow in the wave. The turning circle was compared with Lewandowski's estimation for a planing boat. As a result of this study, it was confirmed that the velocity drop of the developed WPH was not large in a wave, and the vertical acceleration was greatly reduced compared with that of a normal planing boat. The turning circle was somewhat larger than the estimated results for a planing boat, but the overall tendency was the same.